Spatial analysis of the risk of housing and social deprivation - Starček, Simon (Geodetski vestnik, 2025)
Housing and social deprivation is a socially and spatially conditioned phenomenon that extends beyond material scarcity and encompasses limited access to resources, services, and adequate living environments. This form of deprivation is shaped by various factors, among which population ageing, urbanisation, and spatial transformations are pivotal for understanding housing vulnerability and spatial (in)justice. This paper investigates the impact of housing conditions, local economic characteristics, the quality of the residential environment, and ageingrelated demographic processes on the risk index of housing and social deprivation across Slovenian municipalities. Employing geographically weighted regression, we assess local spatial effects and demonstrate that global models tend to underestimate the degree of spatial heterogeneity of these phenomena. The applied cartographic visualisations highlight spatial disparities in the influence of the examined de terminants, thereby providing deeper insights into the patterns of deprivation. These findings can significantly inform the design of more effective and spatially targeted policy measures, particularly tailored to the needs of an ageing population.
Keywords: elderly; geografska obtežena regresija; geographically weighted regression; housing and social deprivation risk index; housing vulnerability; indeks tveganja stanovanjske in socialne prikrajšanosti; prostorska neenakost; Slovenia; Slovenija; spatial inequality; stanovanjska ranljivost; starejši